Differences in physical fitness levels between the classical and the freestyle wrestlers - Baic, M.; Sertic, H.; Starosta, W. (Kinesiology, 2007)
Increasing the physical fitness level is the basic goal of all types of sport preparation. The importance of certain physical fitness abilities for success in a wrestling bout varies in wrestlers of various wrestling styles and age. The aim of this research was to identify the differences between the classical style (Greco-Roman) and the free style wrestlers in the variables assessing physical fitness. The research was conducted on the sample comprised of 107 top-level classical style (n=46) and free style (n=61) wrestlers 17 to 20 years of age, all Polish junior national team members. The measuring instrument consisted of 18 tests, most of them being the test battery of Starosta and Trocewski for advanced wrestlers, aimed at assessing the general and the wrestling-specific physical fitness level. The obtained results were processed by the canonical discriminant analysis and by the univariate analysis of variance (ANOVA). The discriminant factor defined as the strength endurance of the trunk and upper extremities statistically significantly discriminated between the classical and the free style wrestlers. It was found that the group of top-level junior free style wrestlers had statistically significantly more expressed strength endurance of the trunk and upper extremities than the group of top-level junior classical style wrestlers. The authors assumed the obtained results had been induced by the specific features of each wrestling style.